Kepercayaan Diri Mahasiswa PGMI Terhadap Mata Kuliah Matematika - Wildaniati, Yunita (Jurnal Dewantara, 2017)
Mathematics as one of the basic science plays an important role in accelerating mastery of technology science. On the other hand, students to the learning process are also lacking, they cannot yet believe themselves that they are able to study math material in more depth. This research uses descriptive method. The subjects in this study are Strata I students majoring in Teacher Education Madrasah Ibtidaiyah (PGMI) Islamic High School (STAIN) Jurai Siwo Metro 2016/2017 as many as 92 Students. The results show that students' self-confidence is generally good enough. It can be seen from the questionnaire which shows that 28.26% or about 27 students reach the medium criteria, 48.91% or about 45 students reach high criteria, and 21.27% or about 20 students reach very high criteria.